Perceived Promotional Mix And Customer Purchase Intention at Coffee Toffee Bandung Siliwangi - Fathia Rachmah, Amalia; Aprianingsih, Atik (Journal of Business and Management, 2019)
Abstract-  As the tourism sector develops, numerous coffee shops emerged in Bandung city. By that, demand for coffee bean to farmers increased up to 20% in the midst of development. To sustain the industry that has big impact on economic development in the city, this research aims to empower café businesses by taking Coffee Toffee Bandung (CTB) Siliwangi encountered problems pertaining to marketing aspect as the case. CTB Siliwangi is still trying to recognize the market pattern and capture the behavior of its market. Coffee Toffee that targeted young-adult executives, now must adjust and offer the needs and wants of college students as well. By that, CTB can understand the purchase intention of college students by communicating effectively using the promotional mix. This research attempts to examine the current condition of Coffee Toffee Bandung (CTB) Siliwangi potential buyers’ purchase intention and its relationship to Perceived Advertising, Perceived Sales Promotion, Perceived Public Relation and Perceived Personal Selling. Online questionnaire using Likert Scale was designed to 205 respondents in Bandung with purposive sampling method. The questionnaire was measured by Multiple Linear Regression to explain the relationship between dependent variable and independent variables. This study finds that advertising, sales promotion, public relation and personal selling have positive relationship to purchase intention. This study is expected to provide a valuable result regarding the significant impact between advertising, sales promotion, public relation and personal selling towards purchase intention at CTB Siliwangi. However, sales promotion has no significant impact to purchase intention at CTB Siliwangi in this study. The essence of this study is to be useful for practitioners and the academicians to support the strategy and the references of related areas.  Keywords: Purchase Intention, Promotional Mix, Marketing